Demographic Profiles of Animal Bite Cases at a Dedicated Anti-Rabies Hospital in Dhaka City of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Animal bite management are very crucial part in the post prophylaxis treatment.Objective: The purpose of the present study was to see the demographic profile of animal bite cases at a dedicated anti-rabies hospital.Methodology: This retrospective chart review based on secondary data received from animal bite register was conducted in the Department of Microbiology at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2014 to December 2015 for a period of two years. All relevant data were noted from the registered record.Result: A total number of 17688 cases were collected from the register log book of animal bite. The mean age with standard deviation was 24.42±17.22 with the range of 1 to 99 years. The ratio between male and female was 2.33:1. The most common animal bite was dog bite which was 13574(76.7%) cases followed by cat, monkey, fox and weasel bite which were 3667(20.7%) cases, 163(0.9%) cases, 39(0.2%) cases and 22(0.1%) cases respectively. Lower extremity was the most site of bite by the animals which was 12936(73.1%) cases followed by upper extremity, waist, head & neck, face and trunk which were 3592(20.3%) cases, 428(2.4%) cases, 155(0.9%) cases, 116(0.7%) and 114(0.6%) cases respectively. The most common category of bite was category II which was 11800(66.7%) cases.Conclusion: In conclusion male young adult person bite by dog with category II are the most common victims of animal bites seeking for treatment.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 135-139